MANAJEMEN DAKWAH MASJID NURUL HIDAYAH KABUPATEN KERINCI : HERLINA - herlina, Herlina (Qawwam : The Leader's Writing, 2023)
This research is field research with a qualitative approach. Research data was obtained from primary data sources (Ta'mir Great Mosque Kalianda and Jama'ah) and secondary data sources (observation, interviews, documentation). After the data was collected, the researcher used the Miles and Huberman model of data analysis, namely data reduction. , data display (data presentation), and conclusion (drawing conclusions). The results of this research show that in general it can be said that this mosque has not yet optimally functioned as a district mosque, but from the perspective of missionary management, the Kalianda Great Mosque has implemented management functions as evidenced by the planning aspect, it already has a clear work program, and from the organizing aspect it has determined The administrators are in accordance with their fields, from the aspect of mobilization the chairman of Ta'mir has carried out his main duties, including motivating, guiding and communicating with other administrators, from the aspect of supervision they carry out an evaluation in the form of an accountability report (LPJ) at the end of the management of the Kalianda Grand Mosque.